The Effectiveness of Lecture Media and Poster Media Education Methods in Preventing Anemia in Female Students at the Darul Wustha Islamic Boarding School - Asmanidar, Asmanidar; Rasima, Rasima; Julissasman, Julissasman; Hasritawati, Hasritawati (LEMBAGA KAJIAN PEMBANGUNAN PERTANIAN DAN LINGKUNGAN (LKPPL), 2024)
Anemia in adolescent girls is still quite high, according to the World Health Organization (WHO), the prevalence of anemia in the world ranges from 40-88%. According to WHO, the incidence of anemia in adolescent girls in developing countries is around 53.7% of all teenage girls, anemia often attacks teenage girls due to stress, menstruation, or late meals. Data on the prevalence of anemia in teenage girls for the South Aceh Provincial Health Office is not yet available, as is the prevalence for female students at the Darul Wustha Islamic Boarding School Dayah, West Labuhan Haji District. This is because routine monitoring of anemia has never been carried out. However, the results of research that has been conducted in several areas in South Aceh still show a high incidence of anemia in adolescent girls. Zubir's 2018 study of Adolescent Girls at the AsSyifa School Health Vocational School in Banda Aceh showed that 44% had moderate anemia. Mirani's 2021 study found that the prevalence of anemia in female adolescents with iron deficiency in Langsa City was 33.7%. Objective: To determine the effectiveness of knowledge about anemia before and after providing counseling using lecture methods and poster media to female students at the Darulwustha Islamic Boarding School Dayah, West Labuhanhaji District, South Aceh Regency. This study used a quasi-experimental method and utilized a pretest and posttest design, namely by taking initial measurements before and after treatment was given. The population in this study were all new female students totaling 40 people. The results of this study with a pre-test value of 7.96, a post-test value of 17.18, and a PValue value of 0.000.